Uncertainty model unfalsification - Kosut, R.L.; Anderson, B.D.O. (Proceedings of the 36th IEEE Conference on Decision and Control, 1997)
The main contributions presented are (i) to widen the classes of model sets for which necessary and sufficient conditions for uncertainty model unfalsification can be obtained, and (ii) to display the effect of different assumptions concerning the modeling error on the curves defining the boundary of unfalsified models (the optimal uncertainty tradeoff curve) for the same underlying data set.